2010
DOI: 10.1161/hypertensionaha.109.143867
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Arterial Stiffness Should Discriminate Between Systolic and Diastolic Pressure Ranges

Abstract: Abstract-Arterial stiffening plays an important role in the development of hypertension and cardiovascular diseases. The intrinsically nonlinear (ie, pressure-dependent) elastic behavior of arteries may have serious consequences for the accuracy and interpretation of arterial stiffness measurements and, ultimately, for individual patient management. We determined aortic pressure and common carotid artery diameter waveforms in 21 patients undergoing cardiac catheterization. The individual pressure-area curves w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 45 publications
6
77
0
1
Order By: Relevance
“…For example, the increase in pressure from diastolic pressure to systolic pressure during a single cardiac cycle could result in a variation of 0.7-4 m/s of PWV (i.e., without any change in vascular wall property) [9,10]. This variability is mainly caused by the organization of elastin, collagen, and vascular smooth muscle cells of the media.…”
Section: Pwv and Operating Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…For example, the increase in pressure from diastolic pressure to systolic pressure during a single cardiac cycle could result in a variation of 0.7-4 m/s of PWV (i.e., without any change in vascular wall property) [9,10]. This variability is mainly caused by the organization of elastin, collagen, and vascular smooth muscle cells of the media.…”
Section: Pwv and Operating Blood Pressurementioning
confidence: 99%
“…1). Indeed, a steeper slope in pressure-diameter relationship is observed in the elderly compared to younger individuals as pressure dependence varies with age, due partly to the age-related material fatigue, fractures in the elastin lamella, and vascular fibrosis [9,10,15]. …”
Section: Pwv and Operating Blood Pressurementioning
confidence: 99%
“…Arterial elastic behavior, however, is pressure dependent [8][9][10], which may render aPWV, as estimate of diastolic stiffness, less suitable to reflect effective cardiac afterload. Moreover, we previously demonstrated that the degree of the pressure dependency of arterial stiffness may vary considerably between individuals [11], illustrating the need for individualized assessment of this property.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between aortic pressure and size is known to be non-linear and single or dual exponential functions were employed elsewhere. 19,22 However, our choice allows the separation between elastin and collagen regions that is consistent with the structural elements of the wall reflected in serial or parallel hook-on arrangement models. 2,27 The linear regression models for the elastin and collagen regions were adjusted to the pressure-diameter curves with high correlation coefficients (always above 0.9).…”
Section: Discussionmentioning
confidence: 99%